Preparation method of high-quality HgTe colloidal quantum dot ink and film

Through ligand exchange and spin coating, the problems of long-chain ligands in HgTe CQDs films affecting charge transport and film density are solved, achieving the preparation of high-quality films and improving the performance of infrared detectors.

CN119592125APending Publication Date: 2025-03-11KUNMING INST OF PHYSICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622041.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When HgTe CQDs film is applied to infrared detectors, long-chain ligands affect the transmission speed of charge between quantum dots, resulting in a degradation of device performance. At the same time, low-flat, low-density films will introduce interface defects and reduce the carrier migration rate.

Method used

Through ligand exchange, long-chain oleamines are replaced with short-chain organic ligands and halogen ion ligands, reducing surface defects and increasing charge transfer rates. High-quality HgTe CQDs films are prepared in combination with spin coating to ensure the density and smoothness of the film.

Benefits of technology

The charge transfer rate between quantum dots in HgTe CQDs films is achieved, which enhances the photoelectric detection performance of the device, and prepares a film with flat surface, denseness and uniformity, which improves the overall performance of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592125A_ABST
    Figure CN119592125A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of quantum dots, and particularly discloses a preparation method of high-quality HgTe colloidal quantum dot ink and a film, and the preparation method comprises the following steps: taking an HgTe colloidal solution; a ligand solution is prepared, wherein 5 mg of DDAB, 30 mg of HgBr2, 30 mg of HgI2 and 200 [mu] L of beta-ME are added into every 5 mL of the DMF solution, and the ligand solution is obtained through mixing; the HgTe colloidal solution and the ligand solution are mixed, dissolved and oscillated, supernate is removed and cleaned with normal octane, methylbenzene is used as an anti-precipitating agent, after the supernate is removed through centrifugation, precipitates are dried, and final HgTe CQDs powder is obtained; the preparation method comprises the following steps: dissolving HgTe CQDs powder into a DMF (40L) and DMSO (10L) mixed solution again to form ink-like ink, and spin-coating the ink on a spin-coating machine to obtain the film, carrying out surface environment modification by using beta-ME, HgBr2, HgI2, DDAB and other ligands, and blending a quantum dot ink solvent formula to change the surface chemical environment of quantum dots, thereby successfully preparing the compact and uniform HgTe CQD film with small surface roughness (RMS = 7.3 nm).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum dots, and in particular relates to a method for preparing high-quality HgTe colloidal quantum dot ink and film. Background Art

[0002] Colloidal quantum dots (CQDs) are semiconductor nanocrystals with a size of 2-20nm and smaller than the Bohr radius of their excitons, and are coated with long-chain organic ligands (oleylamine, oleic acid, dodecanethiol, etc.). They are "quasi-zero-dimensional" nanomaterials that contain thousands of atoms and have a certain charge on the surface. One or several long-chain organic ligands coated on the surface can protect the quantum dots and improve their dispersion, ensuring that they can be stably placed in the solution.

[0003] HgTe CQDs is a relatively special semiconductor material in the current field of infrared detectors. It has the characteristics of zero band gap, inverted band structure and low electron mass, and has a high electron mobility. The film made of HgTe CQDs is the most critical part that determines the detection performance of the detector. However, when the HgTe CQDs film is used in the detector, the long-chain ligands on the surface will affect the transfer of charges between adjacent quantum dot particles, causing the transfer speed of charges between quantum dots to decrease, resulting in a decrease in the performance of the device. Therefore, when preparing the quantum dot film of HgTe CQDs used in the device, short-chain inorganic and organic ligands are used to replace the long-chain ligands, among which Br - ,I - Ions reduce defect concentration, short-chain β-ME ligands change the surface environment of quantum dots, and DDAB accelerates liquid phase transfer. This improves the charge transfer rate between adjacent quantum dots without destroying the quantum dots or affecting their stability, thereby improving device performance.

[0004] After ligand exchange, HgTe CQDs thin films can be prepared by spin coating. Low flatness and low density thin films will introduce interface defects on the contact surface of the device functional layer, which will cause carriers to recombine during transportation due to the presence of defects, reduce the carrier migration rate, and also reduce the performance of the device. Therefore, it is particularly important to prepare thin films with smooth surface, good density and uniformity. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing high-quality HgTe CQDs ink and film, and to prepare high-quality HgTe CQDs film by ligand exchange and spin coating to solve the problems existing in the background technology. Specifically, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a HgTe CQDs film, comprising the following steps:

[0007] S1 takes HgTe colloidal solution;

[0008] Preparation of S2 ligand solution: Add 5 mg of DDAB and 30 mg of HgBr to every 5 mL of DMF solution. 2 、30mg HgI 2 , 200 μL β-ME, mixed to obtain a ligand solution;

[0009] S3: The HgTe colloidal solution and the ligand solution are mixed and shaken, the supernatant is removed, and the mixture is washed with n-octane, and toluene is used as a reverse precipitant. After the supernatant is removed by centrifugation, the precipitate is dried to obtain the final HgTe CQDs powder;

[0010] S4 re-dissolves the HgTe CQDs powder into a mixed solution of DMF and DMSO to form an ink-like ink, and spin-coats the ink on a spin coater to obtain a thin film.

[0011] Furthermore, in step S1, the concentration of the HgTe colloidal solution is 10 mg / mL, and in step S4, the volume ratio of DMF to DMSO is 4:1.

[0012] Furthermore, in step S1, the method for preparing the HgTe colloidal solution comprises the following steps:

[0013] (1) Preparation of TOP-Te solution

[0014] Tellurium powder and trioctyl phosphine (TOP) were mixed in a three-necked flask and transferred to a Schlenk tube system. The mixture was heated under vacuum until all the tellurium powder was dissolved and cooled to room temperature to obtain a TOP-Te solution.

[0015] (2) Synthesis of HgTe colloidal solution

[0016] The first step is to add HgCl into the container. 2 , oleylamine and DDT and degassed at 120 °C for 2 h, and then injected with TOP-Te solution in an Ar gas environment at 80 °C to complete the nucleation reaction;

[0017] In the second step, the mixed solution of TOP-Te and oleylamine is continuously injected into the container. After the reaction is carried out for a certain period of time, it is quenched with a mixture of tetrachloroethylene and mercaptopropionic acid. After cooling naturally to room temperature, the obtained HgTe CQDs solution is added with isopropanol for reverse precipitation centrifugation. After the supernatant is poured out, the precipitate is dissolved and dispersed in n-octane to obtain a HgTe CQDs colloidal solution.

[0018] Furthermore, the HgTe CQDs film obtained by any of the preparation methods described in the present invention is used in the preparation of infrared detectors.

[0019] The present invention also provides an infrared detector, which contains a layer of HgTe CQDs film obtained by any of the preparation methods described above.

[0020] Furthermore, the present invention provides a method for preparing the infrared detector, characterized in that the preparation method comprises the following steps: on a clean quartz substrate, Cr, Au, NiOx, ZnO, and ITO are grown in sequence by target magnetron sputtering, HgTe CQDs film is spin-coated with the prepared ink, Au and ITO are used as electrodes, NiOx is used as a p-type hole transport layer, HgTe CQDs film is used as a p-type photosensitive layer, and ZnO is used as an n-electron transport layer to construct a device structure of Au / p+-NiOx / p-HgTe CQDs / n-ZnO / ITO.

[0021] The technical effects achieved by the present invention are:

[0022] 1. The present invention adopts a secondary injection method to synthesize monodisperse HgTe CQDs with an average particle size of 5.06 nm, and adopts liquid phase ligand exchange to exchange the long-chain oleylamine on the surface of quantum dots with short-chain organic ligands and halogen ion ligands, thereby reducing surface defects and vacancy defects, improving carrier mobility, and enhancing photoelectric detection performance.

[0023] 2. The present invention uses β-ME, HgBr 2 , HgI 2 , DDAB and other ligands were used to modify the surface environment, and the surface chemical environment of the quantum dots was changed by adjusting the quantum dot ink solvent formula to successfully prepare a dense and uniform HgTe CQD film with a small surface roughness (RMS = 7.3nm). The HgTe CQDs film was used as the photosensitive layer to construct a p+-pn structure, and the device structure was Au / p+-type NiOx / p-type HgTe CQDs / n-type ZnO / ITO. At room temperature, the detection rates under LED light and indoor light as light sources were 4.8×10 8 Jones and 4.0×10 9 Jones. The research of this invention opens up new research paths for surface ligand technology on other CQDs and also provides valuable reference for the development of other high-performance devices based on CQDs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TEM images, crystal surface structure and absorption characteristics of HgTe CQDs; (a) Particle size distribution and TEM image (b) TEM image under dark field (c) TEM lattice fringe image (d) (1 1 1) crystal surface image (e) (1 1 0) crystal surface image (f) Absorption spectrum image;

[0025] Figure 2 HgTe CQDs ligand modification mechanism, film preparation process and AFM characterization. (a) Ligand modification mechanism diagram (b) AFM image of the film (c) Liquid phase modification process diagram;

[0026] Figure 3 Figure 1. Research on the structure and photoelectric properties of HgTe CQDs photodetector. (a) Schematic diagram of the device structure (b) SEM cross-sectional view of the device (c) Schematic diagram of the working principle of the device (d) IV curve of the device under LED light, indoor light and dark conditions (e) Detection rate under indoor lighting LED light (f) Detection rate under LED light;

[0027] Figure 4 Actual photos of HgTe CQDs thin films prepared with different types of ligands; (a) mercaptoethanol and mercuric chloride as ligands (b) mercaptoethanol, dodecyltrimethylammonium bromide, and mercuric chloride as ligands (c) mercaptoethanol, dodecyltrimethylammonium bromide, mercuric chloride, and mercuric iodide as ligands (d) mercaptoethanol, dodecyltrimethylammonium bromide, mercuric bromide, and mercuric iodide as ligands. Specific embodiments

[0028] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0030] Example 1

[0031] 1. Preparation of TOP-Te solution

[0032] 1.276 g of tellurium powder (10 mmol) and 10 mL of TOP (trioctylphosphine) were mixed in a 100 mL three-necked flask in a glove box and transferred to a Schlenk tube system. After three cycles of purging and degassing with argon, the mixture was heated to 100 ° C under vacuum and degassed at this temperature for 1 h. Then, the three-necked flask was purged with argon and heated to 280 ° C. The dark green slurry was stirred at this temperature until all the tellurium powder was dissolved, and then the heating jacket was removed and the three-necked flask was allowed to cool to room temperature under natural ambient conditions. The resulting yellow solution was transferred to a glove box.

[0033] 2. Synthesis of HgTe colloidal solution

[0034] Use the double injection method. Step 1: In a 100 mL three-necked bottle, add 135 mg HgCl 2 15 mL of oleylamine and 1 ml of DDT (dodecyl mercaptan) were degassed at 120 °C for 2 h, and 100 μL of 1 M TOP-Te was injected in an Ar gas environment at 80 °C for 1 min to complete the nucleation.

[0035] In the second step, a mixed solution containing 100 μL 1M TOP-Te and 400 μL oleylamine was quickly injected within 1 min. After the reaction was carried out for 5 min, 15 mL tetrachloroethylene and 60 μL of mercaptopropionic acid (MPA) were added to quench the reaction. After cooling naturally to room temperature, the obtained HgTe CQDs were added with isopropanol for reverse precipitation and centrifugal washing to remove excess oleylamine. Finally, the supernatant was poured off, and the precipitate was dissolved and dispersed in n-octane to obtain a HgTe CQDs colloidal solution.

[0036] Example 2

[0037] 1. Liquid-phase ligand modification and film preparation

[0038] Liquid-phase ligand modification has the characteristics of mild and easily controllable reaction conditions, which can improve the dispersibility and stability of quantum dots, optimize the optical properties of quantum dots, and broaden the application range of quantum dots.

[0039] The specific process of liquid phase exchange is as follows Figure 2 As shown in c,

[0040] S1 measured 5 mL of 10 mg / mL HgTe colloidal solution;

[0041] S2 ligand solution preparation

[0042] Weigh 5 mg of DDAB (dodecyltrimethylammonium bromide), 30 mg of HgBr 2 、30mg HgI 2 , 200 μL of β-ME (mercaptoethanol) was dissolved in 5 mL of DMF (N, N-dimethylformamide) solution to obtain a ligand solution;

[0043] S3: The HgTe colloidal solution and the HgTe colloidal solution were mixed and shaken for 1 min, the supernatant was removed, and the mixture was repeatedly washed with n-octane for 1-2 times, and then toluene was used as a reverse precipitant, centrifuged at 8000 rpm for 5 min, the supernatant was poured off, and the precipitate was dried to obtain the final HgTe CQDs powder;

[0044] The S3 HgTe CQDs powder was redissolved in a DMF (40 μL) / DMSO (10 μL) mixed solution to form an ink-like ink, and the ink solution was spin-coated on a spin coater at 3000 rpm for 1 min to obtain a film with a thickness of about 300 nm.

[0045] The uniform size and good monodispersity of HgTe CQDs are one of the key points to ensure the strong exciton absorption peak and large peak-to-valley ratio, which is also an important factor to ensure the photoelectric detection performance of the device. Figure 1 As shown in a and 1b, HgTe CQDs with a particle size of about 5.1 nm were synthesized by the secondary injection method, and the size was relatively uniform and the monodispersity was good. Figure 1 c is the (1 1 0) and (1 1 1) lattice fringes of HgTe CQDs, whose sizes are 0.232nm and 0.379nm respectively. Figure 1 d and 1e are the spatial structures of HgTeCQDs on the (1 1 0) and (1 1 1) crystal planes, respectively. Figure 1 f is its exciton absorption peak, which is about 2050nm.

[0046] like Figure 2 The HgTe CQDs shown in a are prepared by adding short chains of β-ME, HgBr 2 , HgI 2 Liquid phase exchange is carried out, in which the binding energy of Hg-S, Hg-Br, and Hg-I bonds is stronger than the binding energy of oleylamine and Hg, and the long-chain oleylamine molecules are replaced by the short-chain β-ME, Br - ,I - The carrier mobility is enhanced by substitution. Figure 2 As shown in b, the surface chemical environment of the quantum dots was changed by adjusting the quantum dot ink solvent formula, and a dense and uniform HgTe CQD film with a small surface roughness (RMS = 7.3 nm) was successfully prepared.

[0047] 2. Differences in the effects of films prepared with different ligand types

[0048] The films prepared according to the ligand types and modification methods shown in Table 1 are as follows Figure 4 As shown by Figure 4 It can be seen that among the film samples, the film conditions of samples 1, 2, and 3 are poor adhesion, general adhesion, thin, general adhesion, and thin, respectively. Among them, the film of sample 4 has high adhesion and density and is thick, and is suitable for the photosensitive layer of photodetectors.

[0049] Table 1 The difference in the effect of preparing thin films with different ligands

[0050]

[0051] Example 3 Device Preparation

[0052] On a clean quartz substrate, Cr, Au, NiOx, ZnO, and ITO were grown by target magnetron sputtering in sequence, with thicknesses of 50nm, 50nm, 100nm, and 100nm, respectively. The liquid-phase modified quantum dot ink was spin-coated with a HgTeCQDs film of about 280nm thickness, where Cr was grown to allow Au to better adhere to the quartz substrate. Au and ITO were used as electrodes, NiOx as a p-type hole transport layer, HgTe CQDs film as a p-type photosensitive layer, and ZnO as an n-type electron transport layer, to construct a photovoltaic device structure of Au / p+-NiOx / p-HgTe CQDs / n-ZnO / ITO.

[0053] The present invention uses indoor lighting LED lamps and commercial LED lamps with a wavelength of about 380nm to 780nm calibrated by an ultraviolet power meter as light sources, and uses a Keithley 2400 digital source meter to measure the current signal of the detector. In the response rate test, the LED light source is modulated by an external power supply, and the real-time current response of the detector is read by an oscilloscope.

[0054] The HgTe CQDs photodetector was characterized and its performance analyzed. Figure 3 As shown in a, a back-illuminated structure of quartz / Au / NiOx / HgTe / ZnO / ITO is used. Light enters from the top ITO, where ZnO is the electron transport layer, NiOx is the hole transport layer, and HgTe colloidal quantum dot film is the photosensitive layer, constructing an asymmetric p+-pn structure device. Figure 3 From the SEM image of the device structure in b, we can see that the thickness of the HgTe quantum dot film is about 286nm, the thickness of the NiOx functional layer film is about 100nm, the thickness of the ZnO functional layer film is about 100nm, and the thickness of the ITO functional layer film is about 100nm. Figure 3 In c, the work function of the Au electrode is about -4.7eV, and ITO is an n-type semiconductor material with a work function of about -4.7eV. When light shines on the photodetector, photons are absorbed by the absorption layer, generating electron-hole pairs. Better energy level matching enables photogenerated carriers to migrate to the corresponding electrodes quickly and efficiently. In photovoltaic photodetectors, under the action of the built-in electric field, electrons move to the n-type region (the region with a lower conduction band energy level) and holes move to the p-type region (the region with a higher valence band energy level), thereby forming a photocurrent. Figure 3 In c, under a bias voltage of -1 V, the photocurrent of the indoor light is about 2×10 -3 mA, the photocurrent under LED light source is about 6×10 -3 mA, the detection rate is Figure 3e and 3f, respectively, D*=4.8×10 8 Jones, D* = 4.0 × 10 9 Jones. And the response rates are calculated as R = 1.0 × 10 -3 A / W, R = 1.3 × 10 -3 A / W.

[0055] The present invention synthesizes monodisperse HgTe CQDs with uniform morphology by using a secondary injection method. The internal defects of quantum dots are reduced by liquid phase exchange, and the long-chain oleylamine organic ligand with poor conductivity is exchanged for a short-chain halogen ligand, thereby improving the transmission rate of photogenerated carriers. NiOx and ZnO are selected as hole transport layer and electron transport layer to effectively transport holes and electrons, thereby promoting the separation and transmission of photogenerated carriers. Based on the dense and flat HgTe CQDs film, a high detection rate (D*=4.0×10 9 Jones) and shorter response time (R = 1.3 × 10 -3 These results suggest that low-cost, fast, and sensitive infrared photodetectors based on HgTe CQDs may have applications in thermal and spectral sensing.

Claims

1. A method for preparing a HgTe CQDs thin film, characterized in that: The following steps are involved: S1 takes HgTe colloidal solution; S2 Preparation of ligand solution: Add 5 mg of dodecyltrimethylammonium bromide (DDAB), 30 mg of HgBr2, 30 mg of HgI2, and 200 μL of beta-mercaptoethanol (β-ME) to every 5 mL of N-N-dimethylformamide (DMF) solution and mix to obtain a ligand solution; S3 The HgTe colloidal solution and the ligand solution are mixed and shaken, the supernatant is removed, and the mixture is washed with n-octane, and toluene is used as a reverse precipitant. After the supernatant is removed by centrifugation, the precipitate is dried to obtain the final HgTe CQDs powder; S4 The HgTe CQDs powder is redissolved in a mixed solution of N-N dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to form an ink-like ink, and the ink is spin-coated on a spin coater to obtain a thin film.

2. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the HgTe colloidal solution is 10 mg / mL, and in step S4, the volume ratio of DMF to DMSO is 4:

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing the HgTe colloidal solution comprises the following steps: (1) Preparation of TOP-Te solution Tellurium powder and trioctyl phosphine (TOP) were mixed in a three-necked flask and transferred to a Schlenk tube system. The mixture was heated under vacuum until all the tellurium powder was dissolved and cooled to room temperature to obtain a TOP-Te solution. (2) Synthesis of HgTe colloidal solution In the first step, HgCl2, oleylamine and DDT were added to the container and degassed at 120°C for 2 h. Then, TOP-Te solution was injected into the container under an Ar gas environment at 80°C to complete the nucleation reaction. In the second step, the mixed solution of TOP-Te and oleylamine is continuously injected into the container. After the reaction is carried out for a certain period of time, it is quenched with a mixture of tetrachloroethylene and mercaptopropionic acid. After cooling naturally to room temperature, the obtained HgTe CQDs solution is added with isopropanol for reverse precipitation centrifugation. After the supernatant is poured out, the precipitate is dissolved and dispersed in n-octane to obtain a HgTe CQDs colloidal solution.

4. Application of the HgTe CQDs film obtained by the preparation method according to any one of claims 1 to 3 in the preparation of infrared detectors.

5. An infrared detector, characterized in that: The infrared detector comprises a layer of HgTe CQDs film obtained by the preparation method described in any one of claims 1-3.

6. The method for preparing the infrared detector according to claim 5, characterized in that: The preparation method comprises the following steps: on a clean quartz substrate, Cr, Au, NiOx, ZnO and ITO are grown in sequence by target magnetron sputtering, a HgTe CQDs film is spin-coated with the prepared ink, Au and ITO are used as electrodes, NiOx is used as a p-type hole transport layer, the HgTeCQDs film is used as a p-type photosensitive layer, and ZnO is used as an n-type electron transport layer to construct a device structure of Au / p+-NiOx / p-HgTeCQDs / n-ZnO / ITO.